ANALISIS DESKRIPTIF PENERAPAN METODE TASHILI:: Studi Kasus Pembelajaran Tilawat Al-Qur’an di PP. al-Bahjah Cirebon - Putriyani, Siti Nur Umdati; Rahtikawati , Yayan (Jurnal Al I'jaz, 2024)
Descriptive analysis research of the application of the Tashili method by taking a case study at al-Bahjah Islamic boarding school urgently is that a teacher must have the right learning method for the success of students. The purpose of this study is to explain the learning and learning of tahsin Al-Qur'an using the Tashili method at al-Bahjah Islamic boarding school. This research uses qualitative methods with data processing in the form of descriptive analysis. Observation, documentation, and in-depth interviews with various sources were used to collect data. The results of this study contain two conclusions. First, the learning of tahsin Al-Qur'an with the Tashili method at al-Bahjah Islamic boarding school consists of volume 1, volume 2, volume 3, volume 4, and volume 5. Second, the implementation of tahsin Al-Qur'an with the Tashili method at al-Bahjah Islamic boarding school uses an individual approach, individual classical, pure reading and listening, and reading and imitating. With these two conclusions, the application of the Tashili method at al-Bahjah Islamic boarding school tends to emphasise the potential of students according to their respective scientific capacities in a categorised manner.